Relevansi Hukum Adat Kei Larvul Ngabal Dalam Pembaharuan Hukum Pidana Nasional - Rudini Hasyim Rado; Marlyn Jane Alputila (Fakultas Hukum Universitas Islam Indonesia, 2022)
This research focuses on exploring and elevating the values of Kei Larvul Ngabal indigenous law in criminal law reform, by proposing 2 (two) problem formulations. First, how is the existence of Larvul Ngabal indigenous law in the Kei community? Second, how is the relevance of the Kei indigenous criminal law in the reform of the national criminal law? The research method used is normative juridical by reviewing written and unwritten criminal laws and regulations. While the data analysis is inductive and qualitative. It is concluded that the indigenous law of Larvul Ngabal and Sasa Sor Fit is an indigenous criminal law that is agreed upon and is binding on the community, hence if it is violated, it is subject to indigenous sanctions in the form of fines, dada, and gong. Included in the drafting of the Criminal Code without reducing the nature of the material legality principle, if there are several customary laws of Larvul Ngabal including maryain vo ivun (sexual intercourse outside of marriage resulting in pregnancy) it can be reconsidered to contribute to the ius constituendum of future criminal law. Key Words: Indigenous criminal law; larvul ngabal; criminal law reform AbstrakPenelitian ini difokuskan untuk menggali dan mengangkat nilai-nilai hukum adat Kei Larvul Ngabal dalam pembaharuan hukum pidana, dengan mengajukan 2 (dua) rumusan masalah. Pertama, bagaimana eksistensi hukum adat Larvul Ngabal dalam masyarakat Kei? Kedua, bagaimana relevansi hukum pidana adat Kei dalam pembaharuan hukum pidana nasional? Metode penelitian yang digunakan yaitu yuridis normatif dengan mengkaji peraturan perundang-undangan pidana baik tertulis maupun tidak tertulis. Sedangkan analisis data bersifat induktif dan kualitatif. Disimpulkan bahwa hukum adat Larvul Ngabal beserta Sasa Sor Fit adalah hukum pidana adat yang disepakati dan berlaku mengikat bagi masyarakatnya, bilamana dilanggar dikenai sanksi adat berupa denda, dada, serta gong. Termasuk dalam penyusunan R-KUHP tanpa mereduksi hakikat asas legalitas materiel, sekiranya terdapat beberapa hukum adat Larvul Ngabal diantaranya maryain vo ivun (persetubuhan di luar perkawinan mengakibatkan hamil) dapat dipertimbangkan kembali untuk berkontribusi dalam ius constituendum hukum pidana yang akan datang. Kata kunci: Hukum pidana adat; larvul ngabal; pembaharuan hukum pidana